TEKTONOSTRATIGRAFI CEKUNGAN OMBILIN SUMATERA BARAT - Mulyana, Budi (Fakultas Teknik Geologi Universitas Padjadjaran, 2005)
Ombilin Basin is represent basin intramontane which limited by volcano-plutonic of Bukit Barisanand zona of Sumatera Fault system which representing a active strike-slip fault zone in west andmetasedimen rock in. Form of fisiography Ombilin Basin show a hilly at part of edge of east-west untilto north with precipitous morphology and level-off continent. Ombilin Basin basement is divided twopart, that is structured basement by Mergui terrain and Woyla terrain. Eldest Basement of Ombilin Basinis Formation of Limestone crystallin of Silungkang (age Perm) which laid bare at Tanah Hitam whichrepresent the part of Mergui terrains continent.Tectonism of Ombilin Basin is started at Paleogen related to peripatetic Southeast Asia tectonismwhich moving of India Block to northern. Early Paleogen, Ombilin Basin is formed with early motion oftranstensional effect of strike-slip fault motion of duplex regional, that is graben part of northeastOmbilin Basin. Motion of strike-slip fault are Sitangkai fault and Silungkang fault where this faultsmotion result attraction style in the form of normal fault by terrace to left north-south. This fault patterncontrol forming of first basin cause to be formed its faults which instructing northwest-southeast, northsouth,and northeast-soutwest of west-east. Tectonostratigraphy Ombilin Basin is represent full grabenwith set of deposits syn-rift tectonostratigraphy and of post-rift deposits continue at mechanism oftransgressive in the early Neogen.